Distribution of personal wealth in Ireland - evidence reexamined - comment - Harrison, M.J. (Economic & Social Studies, 1976)
The points made by Chesher and McMahon (hereafter CM) concerning thestatistical test procedure used by Harrison and Nolan (hereafter HN) in their 1975 paper are valid. Indeed, HN have been aware o f them for some time. It is, of course, regrettable that HN did not make this known before receipt of the CM paper.
Keywords: Personal wealth; Estates